Cognitive Science in Education and Alternative Teaching Strategies - Boris Abersek, Andrej Flogie, Metka Kordigel Abersek, Magdalena Sverc (Cambridge Scholars Publishing, 2017)
Cognitive science deals with such questions as 'How do we think?' and 'How do we learn, memorize, dream?'. It tackles the subject of human mentality by connecting discoveries from a range of disciplines that shed light on cognitive occurrences and the learning process. Cognitive science unites the fields of neuroscience, psychology, philosophy, linguistics, artificial intelligence, and social sciences. This book, aimed mostly at teachers, will provoke cognitive dissonance and intellectual unease, as it explores cognitive theories and allows teachers to update and internalise their 'in-head theories', embedded from their own school years. In order for this to happen, this volume provides information on new experiences of alternative teaching practices. Creating conditions for gaining these teaching experiences is the primary function and fundamental mission of politics in the field of education.